Epilepsy 12 – United Kingdom collaborative clinical audit of health care for children and young people with suspected epileptic seizures (PRELIMINARY RESULTS). (24th May 2012) - Ranmal, R; Waldron, B; Flower, D; Colaco, F; Bowyer, K; Gilmore, E; Maini, R; Williams, FLR; Brown, A; Notghi, L; Martin, K; Chin, R; et al.
Abstract : Aims: To assess the quality of paediatric care for UK children, young people and families affected by epilepsies and seizures. Methods: In 2009, the RCPCH 'Epilepsy 12' Audit began a pragmatic audit of UK paediatric epilepsy care against NICE and SIGN guidelines. A project board representing UK stakeholders invited participation from all relevant local NHS hospital and community paediatric services. Audit domains were: 1. clinical service description; 2. 12 clinical performance indicators and 3. a specially developed patient-related experience measure (PREM). The service description was completed at the onset. Lists of children referred for electro-encephalography helped identify eligible children aged 1 month to 16 years who had received a first paediatric assessment for afebrile paroxysmal episode (s) within a 6 month period from 2009. Retrospective data from case-notes review of the subsequent 12 months were entered onto a web-based database. Children commenced on anti-epileptic medication were invited by letter to complete an anonymised PREM questionnaire. Results: Data collection was completed in November 2011. All 197 audit units and 21 regions enrolled. Participation rates were 98% (193/197) for clinical service description, 94% (186/197) for clinical audit and 87% (172/197) for PREM domains. The clinical cohort consisted of 4991 patients, median age 6.3 years, M:F 54:46%. 44% (2175/4991) of first paediatric assessments occurred within an acute presentation. 19% (974/4991) of children had a documented neurodisability. Diagnosis of paroxysmal episode (s) at first assessment was recorded as: 46% (2298/4991) epileptic; 18% (897/4991) non-epileptic and 36% (1796/4991) uncertain. Diagnosis after 12 months of care was recorded as: 6% (312/4991) single or 'single cluster' epileptic seizure (s); 36% (1774/4991) 2 or more epileptic seizures; 44% (2198/4991) non-epileptic and 14% (707/4991) uncertain. Conclusion: The paediatric epilepsy community, including acute and community services and patient organisations, has contributed to the largest description of the performance of paediatric epilepsy care in the UK to date. From the preliminary analysis, just over half the children with paroxysmal episode (s) presented non-acutely with one third eventually diagnosed as having recurrent epileptic seizures. Over the 12 months of follow-up, diagnosis varied and diagnostic uncertainty decreased. Final results will be placed in the public domain in September 2012.